LE LEADERSHIP FEMININ DE LA DIRECTION SCOLAIRE ET PERFORMANCES DES ECOLIERS DE QUATRIEME PRIMAIRE EN DICTEE FRANÇAISE - Kyangambi, Emmanuel Kenya; SINGO, Henriette KANYINGA; LOFALA, Bienvenu EKILI (IJRDO - Journal of Social Science and Humanities Research, 2022)
The present study probes into the impact of a school administration by woman on her learners’ performances. A questionnaire has been applied to 10 heads of schools (men and women) and to their 4th form primary school pupils a French dictation examination was given to them. Through to multiple regression, it has been discovered that the headmaster’s gender has a weak impact on pupils’ performances. Therefore, instead of tarrying just on womanly presence to be a head of a school, you need possibly review the selection criteria which should not be focused only on gender but the other insignificant assets such as moral values which are specific and/or to consolidate about a woman.